(untitled) (Research, Society and Development, 2021)
This research aimed to describe the use of non-invasive care technologies used by the health team in vaginal birth and to identify the benefits reported by postpartum women after using such technologies. Descriptive study, with a quantitative approach and developed through field research. Data collection was carried out between the months of August and September 2020, using a Microsoft forms form, distributed to possible participants through social networks. A total of 213 mothers over 18 years of age and up to one year postpartum participated in the study. The results show that: 54% of the participants had a university degree, 58% gave birth in the public network, 71% had access to a warm bath during labor, 60% were able to choose the position during childbirth and 50% used the Swiss ball in the pre-partum. It is concluded that non-invasive birth care technologies were used in the participants’ experiences and that their use helped to control pain during this period. It is still necessary to expand the use of these technologies for the benefit of parturients and to improve the quality and humanization of normal birth.